2016
DOI: 10.1542/peds.2015-4458
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Effects of Adenotonsillectomy for Obstructive Sleep Apnea

Abstract: OBJECTIVE: Research reveals mixed evidence for the effects of adenotonsillectomy (AT) on cognitive tests in children with obstructive sleep apnea syndrome (OSAS). The primary aim of the study was to investigate effects of AT on cognitive test scores in the randomized Childhood Adenotonsillectomy Trial. METHODS:Children ages 5 to 9 years with OSAS without prolonged oxyhemoglobin desaturation were randomly assigned to watchful waiting with supportive care (n = 227) or early AT (eAT, n = 226). Neuropsychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 47 publications
2
61
0
2
Order By: Relevance
“…We anticipated that a breathing abnormality during sleep could be related to difficulty in responding to multiple stimuli (e.g., making slower responses), but this was not observed. Nevertheless, our finding of slower simple reaction time is similar to previous studies in children with OSA that showed negative associations between OSA and tests of speed and accuracy (5, 1416, 23). We had anticipated finding significant differences in sustained visual attention and simple reaction time between JIA with and without OSA, but this was not observed.…”
Section: Discussionsupporting
confidence: 91%
“…We anticipated that a breathing abnormality during sleep could be related to difficulty in responding to multiple stimuli (e.g., making slower responses), but this was not observed. Nevertheless, our finding of slower simple reaction time is similar to previous studies in children with OSA that showed negative associations between OSA and tests of speed and accuracy (5, 1416, 23). We had anticipated finding significant differences in sustained visual attention and simple reaction time between JIA with and without OSA, but this was not observed.…”
Section: Discussionsupporting
confidence: 91%
“…However, demonstrations of cognitive impairments have often been less robust than those reported when assessing behavioral outcomes, with some studies failing to detect significant differences between children with and without SDB [29]. For example, the only randomized clinical trial to date that examined the effects of adenotonsillectomy (T&A) treatment for SDB found significant improvements in behavioral functioning after seven months compared to children assigned to a watchful waiting treatment arm, but cognitive/executive-functioning changes were small and less consistent [30,31]. …”
Section: Introductionmentioning
confidence: 99%
“…38 However, even though the long-term implications of cognitive losses are obviously of great concern, relatively fewer studies have attempted to identify markers of cognitive susceptibility, [88][89][90] most likely because of the labor-intensive nature of psychometric testing and the relatively large number of children required for such endeavors. 2,4 Taken together, it appears that the presence of morbidities that have been thus far associated with pediatric OSAS illustrates the complex interactions between biologic pathways activated by the presence of the disease (eg, inflammation, oxidative stress), environmental factors (eg, diet, physical activity, pollution), and genetic determinants (ie, singlenucleotide polymorphisms in relevant genes involved in the pathophysiology of end-organ dysfunction). 91 On the basis of such a conceptual framework, the vast array of novel technologies that allow for unbiased exploration of an exceedingly large number of prospective biomarkers in relatively small biologic samples should encourage researchers and funding agencies alike to invest in prospective real-life studies aimed at discovering, validating, and implementing biomarkers that reliably detect at-risk pediatric OSAS populations and enable timely and effective interventions.…”
Section: Cognitive Morbidity Including Excessive Daytime Sleepinessmentioning
confidence: 99%
“…[2][3][4] Furthermore, evidence of cardiovascular involvement manifesting as endothelial dysfunction, systemic and pulmonary hypertension, and alterations in left ventricular geometry and contractility has been reported, [5][6][7][8][9] along with heightened risk for metabolic perturbations such as insulin resistance, and dyslipidemias, nocturnal enuresis, and excessive daytime sleepiness. [10][11][12][13][14] As a result of OSAS, increases in health-care use and costs have been reported, 15,16 while effective treatment exerts obvious quality-of-life improvements.…”
mentioning
confidence: 99%